In the blink of a pie - Bruns, Catherine (A Maple Syrup Mystery, 2024)
"It's Thanksgiving in Sugar Ridge, Vermont, and Leila Khoury, manager of Sappy Endings Farm, is ready to usher in the holiday season by hosting a pie-baking contest. The day is meticulously planned, from the judging panel to the maple lattes, and Leila can't wait for the entire town to enjoy some sweet treats. But when a neighbor drops dead from sampling a poisoned pumpkin pie, it's not just Leila's perfect day that's in jeopardy- her livelihood is now at stake. And after yet another near-fatal incident, she realizes an even more terrifying truth: the killer wasn't targeting her neighbor but someone even closer to home! Can Leila figure out who's behind the murder before the dough hits the fan?"--